1989
DOI: 10.1159/000146791
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Lymphatics of the Mammalian Heart with Special Reference to the Architecture and Distribution of the Subepicardial Lymphatic System

Abstract: The subepicardial lymphatic system in the rat and dog heart has been investigated by means of scanning electron microscopy. Following application of hydrogen peroxide, the epicardium was removed with a forceps under a dissecting microscope. The subepicardial region contained a well-developed lymphatic system which consisted of the main lymphatic trunks and lymphatic capillaries. The lymphatic trunks of large diameters ran from the apex of the heart to its base. The subepicardial lymphatic capillaries were rami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…As development progresses, lymphatic vessels expand over the dorsal and ventral surfaces and into the myocardium during late embryonic and postnatal stages. In humans, cardiac lymphatics span all layers of the heart (Bradham and Parker, 1973;Shimada et al, 1989), but most cardiac lymphatics in mice are found in the subepicardium and outer myocardium (Flaht-Zabost et al, 2014). Cardiac lymphatic vessels play important roles in maintaining tissue fluid balance and immune surveillance and are implicated in myocardial infarction (MI).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…As development progresses, lymphatic vessels expand over the dorsal and ventral surfaces and into the myocardium during late embryonic and postnatal stages. In humans, cardiac lymphatics span all layers of the heart (Bradham and Parker, 1973;Shimada et al, 1989), but most cardiac lymphatics in mice are found in the subepicardium and outer myocardium (Flaht-Zabost et al, 2014). Cardiac lymphatic vessels play important roles in maintaining tissue fluid balance and immune surveillance and are implicated in myocardial infarction (MI).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In mammals, including humans, all the layers of the heart harbor lymphatic vessels (Fig. 1;Shore 1929;Bradham and Parker 1973;Shimada et al 1989). The subepicardial lymphatics, first described by Rudbeck in the 17th century (Rudbeck 1653), are complemented by a wide capillary network in the myocardium and one located between the endocardium and the layer of Purkinje nerve fibers (Johnson and Blake 1966).…”
Section: Anatomical Structure and Function Of The Cardiac Lymphatic V...mentioning
confidence: 99%
“…43,44 Microscopically, these lymphatics share anatomical and physiological characteristics of other tissues. Subendocardial plexuses are networks of lymphatic capillaries found in the connective tissue between the endocardium and myocardium that form branches running parallel to the endocardial surface.…”
Section: Cardiac Lymphaticsmentioning
confidence: 99%